Multivalent polyrotaxane vectors as adaptive cargo complexes for gene therapy. Issue 7 (14th September 2017) - Ardeleanu, Rodinel; Dascalu, Andrei I.; Neamtu, Andrei; Peptanariu, Dragos; Uritu, Cristina M.; Maier, Stelian S.; Nicolescu, Alina; Simionescu, Bogdan C.; Barboiu, Mihail; Pinteala, Mariana
Abstract : The philosophy to design and construct polyrotaxane carriers, as efficient gene delivery systems. Abstract : This paper describes the philosophy to design, and a procedure to construct polyrotaxane-type gene carriers, together with the proof of their ability to conjunctively cooperate in order to generate cargo-complexes with dsDNA, able to efficiently transfect cultured cells. The main feature of these entities is their functionality as a cargo-complex that chemomimic the histones, and morphomimic the nucleosome. The polyrotaxane contains a PEG axle end-capped with silatrane cages, allowing the threading of nine cyclodextrin units, functionalized with polyethylenimines (PEI, 2 kDa). The obtained ROT-PEI multivalent architecture is similar to a giant PEI polycation, but devoid of the toxicity of large PEIs. To increase the cargo-complexes' versatility and to reduce their cytotoxicity, the study has been complemented with two other types of carriers: (i) including a mixture of PEI and short PEG molecules (ROT-PEI-PEG750 ), and (ii) with PEI branches post-decorated with guanidine or arginine (ROT-PEI-G; ROT-PEI-Arg). The molecular geometry and the overall interactions of the synthesized carriers were investigated in silico . The experimental DNA binding capacity of these carriers in relationship with size, morphology and electrical charge was evaluated. The in vitro tests, showing the cytotoxicity and transfection efficiency of the investigated carriers, provided new information on gene vector design.